Comparisons of radiative transfer schemes for infrared spectra and the region with solar and infrared spectra overlap in RRTMG. (March 2020) - Lin, Han; Wu, Kun; Li, Wenwen
Highlights: Five radiative transfer schemes are compared in infrared spectra using RRTMG. Two methods for handling the overlap of solar and infrared spectra are studied. All schemes are implemented with single column experiment and large-sample test. A new scheme is established to solve the solar energy in longwave spectra. Abstract: Five radiative transfer schemes are compared in infrared spectra using the Rapid Radiative Transfer Model for General Circulation Models Applications (RRTMG). By calculating the root mean squared error of net flux (referred as RMSE(NF)) in various atmosphere, the general accuracy of these schemes ranked from low to high are: non-scattering simplification (NS), the adding method of δ -two-stream discrete ordinate approximation ( δ -2DDA), δ -two-stream variational iteration method ( δ -2VIM), the adding method of δ -four-stream discrete ordinate approximation ( δ -4DDA) and δ -four-stream variational iteration method ( δ -4VIM). And their sensitivities to cloud fraction are decreased in the same order. Furthermore, the accuracy and efficiency of these schemes other than NS are studied under the contexts of using two different methods for dealing with the region where the solar and infrared spectra overlap. As one of the two overlap methods, One Band method (OB), which is used by RRTMG, has no advantage in model efficiency and is about 0.34 (0.41) W/m 2 higher in mean column RMSE(NF) of the δ -two-stream ( δ -four-stream) schemes than Whole Bands method (WB). Moreover, a new scheme, which is simple but adequate to handle the overlap region, is derived to solve the solar energy in longwave spectra.